CLINICAL-PATHOLOGICAL SIGNIFICANCE OF THE BIOMARKERS RRM1, MGMT, TUBB3, AND PTEN IN SEVERAL HISTOLOGICAL SUBTYPES OF SOFT TISSUE SARCOMAS (MATHEMATICAL MODELING OF SURVIVAL BASED ON A SYNTHETIC COHORT) - Guliyeva, T.S.; Safarova, S.I.; Bagirova, Sh.H.; Karimova, G.I.; Giblaliyeva, N.G.; Safarova, R.I. (World of Medicine and Biology, 2026)
Soft tissue sarcomas are rare but highly heterogeneous mesenchymal tumors. In this study, the clinical-pathological significance of the biomarkers RRM1, MGMT, TUBB3, and PTEN in patients with soft tissue sarcomas was evaluated using a model-based statistical approach. A synthetic cohort of 250 patients was created, and overall survival and progression-free survival were analyzed using Kaplan-Meier and Cox proportional hazard models. According to the results obtained, the hazard ratio for overall survival associated with PTEN loss was approximately 1.9, for progression-free survival associated with high TUBB3 expression 1.7, and for low RRM1 expression in gemcitabine-treated patients 0.53. Thus, biomarkers such as RRM1, TUBB3, and PTEN have considerable potential for planning individualized treatment strategies in patients with soft tissue sarcoma; MGMT methylation may serve as a predictive marker in selected cases.
Keywords: soft tissue sarcoma; RRM1; TUBB3; PTEN; MGMT; Kaplan–Meier; Cox model